Micro-Raman analysis of pigments from hunter-gatherer archaeological sites of North Patagonia (Argentina) - Rousaki, Anastasia (2015)
In Northwestern Patagonia, many archaeological sites can be found that testify human occupation by hunter-gatherer groups during the Holocene period. The general purpose of archaeological research in this area is to obtain information on the movements of these groups between the dry steppe and the different sectors in the forests. This paper reports on the results of the first spectroscopic analysis of samples from the archaeological excavation of two hunter-gatherer regions in Northern Patagonia (Traful Lake and Manso River areas). Thirty samples of rock art fragments, grinding tools, shell, raw pigment material, as well as painted ceramics and beads were examined with micro-Raman spectroscopy, complemented with X-ray fluorescence (XRF) analysis. Micro-Raman analysis revealed mostly the use of haematite (Fe2O3) as the red chromophore. The presence of associated minerals and silicates indicated that clay-like material (ochre) was used, instead of pure haematite. Although not fully conclusive, Raman spectroscopic results tend to indicate that in some samples haematite might be formed by heating iron-containing ochres.